Zinc cross-linked hydroxamated alginates for pulsed drug release - Raut, Neha S; Deshmukh, Prasad R; Umekar, Milind J; Kotagale, Nandkishor R (International Journal of Pharmaceutical Investigation)
Introduction: Alginates can be tailored chemically to improve solubility, physicochemical, and biological properties and its complexation with metal ion is useful for controlling the drug release. Materials And Methods: Synthesized N,O- dimethyl, N-methyl, or N-Benzyl hydroxylamine derivatives of sodium alginate were subsequently complexed with zinc to form beads. Hydroxamation of sodium alginate was confirmed by Fourier transform infra-red spectroscopy (FTIR) and differential scanning calorimetry (DSC). Results: The synthesized polymeric material exhibited reduced aqueous, HCl and NaOH solubility. The hydroxamated derivatives demonstrated pulsed release where change in pH of the dissolution medium stimulated the atenolol release. Conclusion: Atenolol loaded Zn cross-linked polymeric beads demonstrated the sustained the plasma drug levels with increased half-life. Although the synthesized derivatives greatly altered the aqueous solubility of sodium alginate, no significant differences in in vitro and in vivo atenolol release behavior amongst the N,O-dimethyl, N-methyl, or N-Benzyl hydroxylamine derivatives of sodium alginate were observed.
Keywords: Atenolol; hydroxylamine derivatives; metal-polymer cross-linked beads; pulsatile release; sodium alginate